(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
ركزت هذه الدراسة على تقدير مستويات الرصاص في بعض عينات الخضار والفاكهة والمأكولات الشعبية وبعض التوابل والأعشاب المجففة التي جمعت من المحلات والباعة في الشوارع الأكثر زحاماً مدينة اللاذقية, وقد تم التحليل باستخدام مطياف الامتصاص الذري ( AAS ). وظهرت النتائج وجود تراكمات للرصاص في بعض عينات الخضار مثل ثمار البندورة ( ppm0.40 ± 0.16 ) وأوراق البقدونس ( ppm0.36 ± 0.13 ) وكان التركيز الأقل في أوراق الملفوف ( ppm0.18 ± 0.09 ). وقد تراوح متوسط التراكيز العالية من الرصاص في بعض عينات الفاكهة بين ( ppm0.47 ± 0.16 ) لثمار العنب و ( ppm0.37 ± 0.09 ) لثمار الفريز، بينما تراوحت المستويات المنخفضة من الرصاص بين ( ppm0.10 ± 0.02 ) في ثمار التفاح و( ppm0.20 ± 0.07) في ثمار المشمش. بينت النتائج وجود تراكمات من الرصاص في عينات من مادة الحلاوة الطحينية ( ppm0.46± 0.06 ) بينما كان متوسط تركيز الرصاص في المادة الخام وهي السمسم ( ppm0.27 ± 0.10 ), وكان تركيز الرصاص في عينات التمر المستورد ( ppm0.38 ± 0.09 ). كانت مستويات الرصاص في المأكولات الشعبية مثل الفول والحمص والبطاطا المقلية طبيعية ( 0.16 -0.17 ), ولكنها كانت عالية في بعض مواد العطارة مثل خلطات البهار المستوردة ( ppm0.51 ± 0.11 ) وعيدان القرفة (ppm0.45 ± 0.08 )، وكان التركيز الأقل في بذور السمسم. This study focused on estimating levels of lead in samples of vegetables, fruits, popular foods, and some spices, seeds, dried herbs and condiments. The samples were collected from shops in Lattakia and from the sides of its streets and roods. Lead was determined by Atomic Absorption Spectrometry (AAS). Results showed accumulation of lead in some vegetables such as tomatoes (0.40 ppm ± 0.16), and parsley (0.36 ppm ± 0.13), while the lowest levels were in cabbage leaves (0.18ppm ± 0.09). Lead concentration was found to be high in some fruits such as grapes (0.47ppm ± 016) and strawberries (0.37 ppm ± 0.7), but it was much lower in other fruits like apples( 0.10ppm ± 0.02 ) and apricots ( 0.20ppm± 0.07 ). Results indicated the accumulation of lead in samples of Halaweh (0.46ppm ±0.06), in contrary to the low levels found in the raw material which is sesame seeds (0.27ppm ± 0.10).The level of lead was also high in imported dates ( 0.38ppm ± 0.09). Lead concentration in the samples of some local popular foods such as parboiled chickpeas and favabeans, and fried potatoes was normal (0.16 – 0.17 ppm). On the other hand, the results indicated high levels of lead in samples of some imported foodstuffs such as spices (0.51ppm± 0.11) and cinnamon (0.45ppm ± 0.08).The concentration of lead was lowest in sesame seeds.